Equivalence Of Translation - Tillaev Zafar Akmalovich (Zien Journals, 2021)
There are always two texts during translation, and one of them is initial and is created independently on the second one, and the second text is created on the basis of the first one with the help of some certain operations - the inter language transformations. The first text is called “the text of original"; the second text is called “the text of translation". The language of the text of original is called “the source language” (SL). The language of the text of translation is called “the target language” (TL)1 . We need to define the most important thing: why do we consider that the text of translation is equivalent to the text of original? For example, why do we speak that the Russian sentence “Мой брат живет в Лондоне" is the translation of the English sentence “My brother lives in London", while the Russian sentence “Я учусь в университете” is not the translation of the English sentence given above - to say in other words - is not equivalent to it? Obviously, the replacement of the text in one language by the text in the other language is not always the translation.
Keywords: Translation; text; equivalent; the equivalence of the original and the translation